A whole-health-economy approach to antimicrobial stewardship: Analysis of current models and future direction - McLeod,M; Ahmad,R; Shebl,NA; Micallef,C; Sim,F; Holmes,A (PLoS Medicine, 2019)
In a Policy Forum, Alison Holmes and colleagues discuss coordinated approaches to antimicrobial stewardship.